Analisis Faktor Penerimaan Pengguna E-Learning SMA Negeri di Kota Blitar Menggunakan Model Unified Theory of Acceptance and Use of Technology (UTAUT) - Diah Destaningrum; Suprapto Suprapto; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
E-learning is an internet application that can connect between educators and learners in a online studi room. E-learning Blitar city to facilitate interaction between school tuition in learning process with the teacher especially in Blitar City. Teacher or an instructor can put learning materials and tasks that must be done by school tuition in a particular place in a web for accessed by the school tuition. Based on the results of interviews from one of the development team, since enactment of e-learning Blitar City users namely students and teachers not have been able to accept any information technology of the new. This can be seen in high school Blitar 1, high school Blitar 2, high school Blitar 3, high school Blitar 4 not all the teachers and students use the e-learning. Unknown factor-factor whatever causing a user not accept any e-learning blitar city. This research be useful to know factor-facktor acceptance users state high school e-learning especially in the Blitar City have applied e-learning. To research it will use the model unified theory of acceptance and use of technology (UTAUT) to know factor-factor anything that affects revenue. The model was obtained from previous studies and adapted in accordance with research. The results of the study based on analysis and discussion is the variable performance expectancy (PE), social influence (SI), facilitating condition (FC). Perceive credibility (PC), and anxiety significant to intention to use.